(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Natural compounds have long been employed as medicines throughout the course of human history. Traditional medicine has employed and still uses natural materials, especially plant treatments, based on practical observations rather than pharmaceutical research. Ixora chinensis (Lam) plant has several important medicinal properties which have not been studied extensively in Bangladesh. The present work has been carried out to evaluate diverse biological actions of the plant extract and identification of pure compounds. The crude powder of leaves and barks of the plant was extracted using absolute methanol. The methanolic extract was subjected to GC-MS to reveal chemical entities present in the extracts and from GC-MS 1,2,3,5-Cyclohexanetetrol was identified. In the present study, methanolic extract of I. chinensis was exposed to investigate antioxidant activity and antimicrobial screening. The antimicrobial screening was performed against gram-positive and gram-negative bacteria including fungus by using disc diffusion technique. The extract of I. chinensis showed mild antimicrobial activity in reference to standard kanamycin and ketoconazole. The results of the present study exhibited high phenolic content (498.8 mg/g) in the methanolic extract compared to gallic acid. Total phenolic content (TPC) of a sample indicates potency of antioxidant. TPC value (224.81 mg GAE/g of sample) of the present study exhibits higher total flavonoid content. The results indicate that the extracts of I. chinensis have lower antioxidant property in respect of total flavonoids content. Antioxidant activity was also measured using DPPH free radical scavenging activity. IC50 value of the methanolic crude extract was found to be 129.128 µg/mL. The data suggested that the crude methanolic extracts possess mild anti-bacterial and antifungal activities with moderate antioxidant activity. Bangladesh Pharmaceutical Journal 28(1): 20-27, 2025 (January)